Boxing for Parkinson's Disease: Has Implementation Accelerated Beyond Current Evidence? - Morris, Meg E.; Ellis, Terry D.; Jazayeri, Dana; Heng, Hazel; Thomson, Andrea; Balasundaram, Arun Prasad; Slade, Susan C. (Frontiers in Neurology, 2019)
Background: Exercise and physical activity are argued to promote neural plasticity in Parkinson’s disease (PD), with potential to slow disease progression. Boxing for PD is rapidly growing in popularity. Objectives: (i) To evaluate evidence on benefits and risks of boxing exercises for people living with PD and (ii) to appraise websites for evidence of global implementation of this intervention. Data Sources: We searched AMED, CINAHL, Cochrane, EMBASE, EMCARE, Health and Medical Collection via ProQuest, MEDLINE, and PEDro electronic databases for the research literature. Websites were also searched for evidence of successful implementation of boxing for PD. Study Selection: Published research and websites were considered if they reported data on adults with PD and boxing as an intervention. Data Extraction: For the literature review, two reviewers independently extracted data on study characteristics and intervention content. Risk of bias was assessed with the PEDro scale and Joanna Briggs Checklist. We conducted a quality appraisal of websites using the QUality Evaluation Scoring Tool (QUEST). Data Synthesis: Two studies, with a total of 37 participants, met the review eligibility criteria for the literature review. Risk of bias was low in these trials. Balance confidence, mobility, and quality of life were reported to improve with community-based boxing training programs delivered in 24-36 sessions over 12 weeks. PD medications were not always documented and some elements of the boxing interventions were incompletely reported against the CERT (Consensus on Exercise Reporting Template). Nine websites advocating boxing programs for PD were also evaluated. The QUEST analysis showed low-level quality, and little scientific evidence verifying findings, despite positive reports. Limitations: In the published literature, findings were limited due to the small number of included studies and participants. Websites were numerous yet often lacked verifiable data. Conclusions: Despite the recent growth in the popularity of boxing for PD and some positive findings, there is limited evidence of efficacy. Risks and disease-specific modifications have not been reported. Safety guidelines and health professional training are key considerations for implementation.